Physiological and Transcriptome Analyses Reveal the Protective Effect of Exogenous Trehalose in Response to Heat Stress in Tea Plant (Camellia sinensis) - Shizhong Zheng; Chufei Liu; Ziwei Zhou; Liyi Xu; Zhongxiong Lai (Plants, 2024)
It is well known that application of exogenous trehalose can enhance the heat resistance of plants. To investigate the underlying molecular mechanisms by which exogenous trehalose induces heat resistance in C. sinensis, a combination of physiological and transcriptome analyses was conducted. The findings revealed a significant increase in the activity of superoxide dismutase (SOD) and peroxidase (POD) upon treatment with 5.0 mM trehalose at different time points. Moreover, the contents of proline (PRO), endogenous trehalose, and soluble sugar exhibited a significant increase, while malondialdehyde (MDA) content decreased following treatment with 5.0 mM trehalose under 24 h high-temperature stress (38 °C/29 °C, 12 h/12 h). RNA-seq analysis demonstrated that the differentially expressed genes (DEGs) were significantly enriched in the MAPK pathway, plant hormone signal transduction, phenylpropanoid biosynthesis, flavone and flavonol biosynthesis, flavonoid biosynthesis, and the galactose metabolism pathway. The capability to scavenge free radicals was enhanced, and the expression of a heat shock factor gene (HSFB2B) and two heat shock protein genes (HSP18.1 and HSP26.5) were upregulated in the tea plant. Consequently, it was concluded that exogenous trehalose contributes to alleviating heat stress in C. sinensis. Furthermore, it regulates the expression of genes involved in diverse pathways crucial for C. sinensis under heat-stress conditions. These findings provide novel insights into the molecular mechanisms underlying the alleviation of heat stress in C. sinensis with trehalose.